Diagnostic Accuracy of Core Needle Biopsy versus Surgical Biopsy in Breast Cancer: Evidence-Based Case Report - Ita Marlita Sari; Fitri Arianti; Muhammad Ilham Saputra; Hana Fajri Alfian; Dhergy Hildan; Yasmin Nur Aqila (UNUSA Press, 2026)
Introduction: Breast cancer is the most common type of cancer in women. A definitive diagnosis of breast cancer is made through histopathological examination, considered the gold standard, which involves performing a biopsy. Several biopsy techniques are available, including core needle biopsy and surgical biopsy. Currently, more cost-effective and minimally invasive biopsy methods are needed to improve patient comfort without compromising diagnostic accuracy. This study aims to assess the accuracy level of the core needle biopsy procedure in establishing a diagnosis of breast cancer, especially in determining the type and grade of tumor, by comparing it with surgical biopsy. This Evidence-Based Case Report was conducted through a literature search in PubMed, Cochrane, and ProQuest databases, using previously formulated keywords. Case: A 45-year-old woman presented to Hospital Z complaining of breast pain. A physical examination revealed a lump in her right breast that had been steadily enlarging for the past two months, accompanied by nipple discharge. The patient was unmarried and had a family history of breast cancer, including her grandmother. Based on these findings, the doctor suspected breast cancer and recommended a biopsy to confirm the diagnosis. Hospital Z offers two biopsy options: core needle biopsy (CNB) and surgical biopsy. The patient chose the core needle biopsy because, based on information obtained online, it was considered more affordable than surgical biopsy. Discussion: The accuracy of core needle biopsy was evaluated based on sensitivity and specificity values. In assessing the accuracy of estrogen receptor determination, the first article showed a sensitivity of 95% and a specificity of 67%, while the second article reported a sensitivity of 100% and a specificity of 92%. For progesterone receptors, sensitivity and specificity were 98% and 69%, respectively, in the first article, and 94% and 86% in the second article. Meanwhile, for HER2 receptors, sensitivity and specificity were recorded at 75% and 98% in the first article, and 83% and 100% in the second article. Conclusions: The core needle biopsy procedure demonstrated a high level of accuracy, both in terms of sensitivity and specificity, in determining tumor type and grade through estrogen, progesterone, and HER2 receptor examination, when compared with surgical biopsy. Therefore, core needle biopsy can be an effective, minimally invasive, and more cost-efficient diagnostic alternative in breast cancer evaluation.